Neutrinoless double beta decay sensitivity of the XLZD rare event observatory - Aalbers,J; Abe,K; Adrover,M; Ahmed,Maouloud S; Akerib,DS; Al,Musalhi AK; Alder,F; Althueser,L; Amaral,DWP; Amarasinghe,CS; Ames,A; Andrieu,B; et al. (Journal of Physics G: Nuclear and Particle Physics, 2025)
The XLZD collaboration is developing a two-phase xenon time projection chamber with an active mass of 60–80 t capable of probing the remaining weakly interacting massive particle-nucleon interaction parameter space down to the so-called neutrino fog. In this work we show that, based on the performance of currently operating detectors using the same technology and a realistic reduction of radioactivity in detector materials, such an experiment will also be able to competitively search for neutrinoless double beta decay in 136Xe using a natural-abundance xenon target. XLZD can reach a 3σ discovery potential half-life of 5.7 × 1027 years (and a 90% CL exclusion of 1.3 × 1028 years) with 10 years of data taking, corresponding to a Majorana mass range of 7.3–31.3 meV (4.8–20.5 meV). XLZD will thus exclude the inverted neutrino mass ordering parameter space and will start to probe the normal ordering region for most of the nuclear matrix elements commonly considered by the community.